MASYARAKAT CERDAS SADAR ARSIP: PENDAMPINGAN PENGELOLAAN ARSIP MELALUI METODE ENKAPSULASI DI DESA PENANGGUNGAN, KECAMATAN TRAWAS, KABUPATEN MOJOKERTO - Nurany, Fierda; Kurniawan, Bagus Ananda; Prasetijowati, Tri; Fitriawardhani, Tira; Fadeli, Muhammad; Indah, Nur; Bayu, Gede; Aristatiyanto, Bela; Sayyidina, Luanna; Cholifattul, Nurul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
The archive management assistance activity through the encapsulation method in Penanggungan Village, Trawas District, Mojokerto Regency, is part of the community service of Bhayangkara University Surabaya which aims to increase the understanding, awareness, and skills of the community as well as village officials in caring for important archives so that they are more durable and protected from physical damage. The implementation method was carried out through socialization stages regarding the importance of archives, technical demonstrations of encapsulation using simple materials such as astralon plastic, double tape, rags, cutters, rulers, and water sprays, as well as independent practice by participants with direct assistance from resource persons from the Archive Aware Community Forum (Forkmasa) of Bhayangkara University Surabaya. The results of the activity showed an increase in the ability of participants to protect documents, a growing awareness of the value of archives as a source of information and legal evidence, and an improvement in the neatness of village administration. This activity also opens up insights into the digitization of simple archives as the first step in digital transformation. The conclusion of this community service emphasizes that the encapsulation method is effective, cheap, and easy to apply at the village level, as well as encouraging the formation of an archival-aware culture, strengthening village governance, and supporting transparency, accountability, and preservation of valuable information for future generations.